Leading everyday complexity - Boesen-Muhonen, Kira (2020)
People around the globe perceive that the world around us is becoming more and more complex all the time. It has become a mantra, which we hear all the time and everywhere. What does it really mean, and what can we do about it, other than just keep repeating it everywhere? There might be a risk that we are using complexity as a general explanation to almost everything, with a supposition that it is all beyond our power. If we don´t understand the essence of what we are dealing with, it is much more difficult to nourish creativity and confidence which would help us to cope with it. Could we learn to bear with complexity as an everyday normal condition, to which we have power over? This qualitative case study tries to understand the complexity and complexity leadership in Savonlinnan Taidelukio, a senior secondary school with a special emphasis on music or visual arts. The purpose of the study is to find out, mainly by interviewing teachers, how the participants understand and experience the complexity and what kind of leadership practices do they find supportive to cope with complexity in their daily working lives. These interview results are compared with four (4) theoretical aspects from complexity and transformational leadership with an aim to build a better understanding of the phenomenon and to find possible connections between the practie and the theories.